Guide to health and safety for European works councils (Brussels, 1996)
"Health and safety at work is a key issue for European Works Councils (EWCs). Through it, employees’ representatives can come to grips with the workplace realities of the people they represent, and management can be taken to task on crucial aspects of company strategy, like subcontracting, work organization, the reduction and organization of working time. Employees’ representatives will be faced with a series of challenges in taking these debates to a successful conclusion. The TUTB’s Guide to Health and Safety attempts to address some of these challenges: – it suggests ways forward and areas where transnational trade union action is possible; – it suggests questions which can be used to elicit vital information on the company, the group, its business lines and potential health and safety issues; – it identifies elements of a common language on prevention in the Community directives; – it provides information on existing voluntary agreements for EWCs."